Structural features of phosphate and sulfate modified zirconia prepared by sol-gel route - Kawaguti, C. A.; Chiavacci, L. A.; Pulcinelli, Sandra Helena [UNESP]; Santilli, Celso Valentim [UNESP]; Briois, V (Springer, 2004)
This paper describes the effect of sulfate, phosphate and nitrate complexing ligands on the structural features of amorphous xerogels and on the crystallization of metastable zirconia phases during the xerogel-ceramic conversion. Powdered samples were prepared by a sol-gel route using zirconyl chloride precursors chemically modified by complexing ligands. The structural evolution of ZrO2 phases as function of firing temperature was analyzed by XRPD, EXAFS and P-13 NMR/MAS. The experimental results show the formation of metastable t-ZrO2 during the low firing temperature of xerogels modified by sulfate or phosphate groups. The martensitic tetragonal-monoclinic transformation occurs during desorption of sulfate groups. The largest temperature interval of stability of metastable tetragonal zirconia was observed for phosphate-modified xerogels.
Keywords: sol-gel process; zirconia tetragonal phase